2021
DOI: 10.15252/embr.202153210
|View full text |Cite
|
Sign up to set email alerts
|

EMC is required for biogenesis of Xport‐A, an essential chaperone of Rhodopsin‐1 and the TRP channel

Abstract: The ER membrane protein complex (EMC) is required for the biogenesis of a subset of tail anchored (TA) and polytopic membrane proteins, including Rhodopsin-1 (Rh1) and the TRP channel. To understand the physiological implications of EMCdependent membrane protein biogenesis, we perform a bioinformatic identification of Drosophila TA proteins. From 254 predicted TA proteins, screening in larval eye discs identified two proteins that require EMC for their biogenesis: fan and Xport-A. Fan is required for male fert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Based on the results of (Gaspar et al , 2022) and the results described here we favor a model where Xport-A acts as chaperone during the biogenesis of Rh1, at a transient step, when the TMDs 1-5 of Rh1 are already inserted in the ER membrane, but TMDs 6-7 are not yet inserted or at least not yet present in Rh1 structure. Interactions of Xport-A with Rh1 TMD1-5 must be essential to stabilize the TMDs of Rh1 but also to stabilize the N terminal ER luminal domain of Rh1 and the beta-loop-beta motif between TMD4 and TMD5, allowing for the correct folding and biogenesis of Rh1.…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…Based on the results of (Gaspar et al , 2022) and the results described here we favor a model where Xport-A acts as chaperone during the biogenesis of Rh1, at a transient step, when the TMDs 1-5 of Rh1 are already inserted in the ER membrane, but TMDs 6-7 are not yet inserted or at least not yet present in Rh1 structure. Interactions of Xport-A with Rh1 TMD1-5 must be essential to stabilize the TMDs of Rh1 but also to stabilize the N terminal ER luminal domain of Rh1 and the beta-loop-beta motif between TMD4 and TMD5, allowing for the correct folding and biogenesis of Rh1.…”
Section: Resultssupporting
confidence: 57%
“…4A) are a series of mutants which lead to an increasingly more hydrophobic TMD of Xport-A, progressively bypassing the EMC requirement for membrane insertion. We have also shown that Xport-A 2L and 4L rescue the expression of Rh1 in EMC mutant cells (Gaspar et al , 2022), but in both cases these rescues were only partial, suggesting that these 2L and 4L mutants have reduced function, although they are inserted into the membrane, even in EMC mutant cells (Gaspar et al , 2022). In Fig.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations